Venous and arterial thrombosis in patients receiving immune checkpoint inhibitors - Anouk van Lent; Rebeca Puscasu; Karin A. H. Kaasjager; Saskia Haitjema; Britt B. M. Suelmann; Marianne C. Verhaar; Meriem Khairoun; Gurbey Ocak (PLoS ONE, 2025)
Background Immune checkpoint inhibitors (ICPi) have been associated with a prothrombotic and pro-atherogenic tendency which could lead to an increased risk of thrombosis. The aim of this study was to investigate the incidence of venous and arterial thrombosis (myocardial infarction or ischemic stroke) in patients who used ICPi as compared with the general population. Furthermore, we investigated the association between the occurrence of venous or arterial thrombosis and mortality. Methods Patients receiving immune checkpoint inhibitors ICPi between January 1, 2013, and May 31, 2020, at the University Medical Center Utrecht, the Netherlands, were included in this study. Indirect standardization was used to compare the incidence rates of venous and arterial thrombosis in patients who used ICPi to the age- and sex weighted incidence rates in the general population. Time-dependent Cox proportional hazard regression model was used to calculate Hazard ratios (HRs) with 95% CIs to investigate the association between the occurrence of a venous or arterial event after start of an ICPi and mortality. Results The age- and sex weighted incidence rates in 663 patients who used ICPi as compared to the general population was 22.7-fold (95% CI 16.6–31.0) increased for venous thrombosis, 3.0-fold (95% CI 1.2–7.1) increased for myocardial infarction, and 3.2-fold (95% CI 1.6–5.7) increased for ischemic stroke. After adjustment, the all-cause mortality risk was 2.3-fold (95% CI 1.5–3.5) increased for patients who were diagnosed with venous thrombosis during follow-up and 2.2-fold (95% CI 1.1–4.1) increased for patients who were diagnosed with arterial thrombosis during follow-up as compared with patients without venous or arterial thrombosis during follow-up. Conclusion Patients receiving ICPi have elevated risks of venous thrombosis and arterial thrombosis. Occurrence of venous thrombosis or arterial thrombosis during treatment with ICPi is associated with an increased mortality risk.